Lead-free halide double perovskites for sustainable environmental applications - Ruby Jindal; Archana Tripathi; Chandra Mohan; Alka Garg; Rajender S. Varma (Chemical Physics Impact)
The development of renewable energy sources has become a crucial objective in today's world due to increasing environmental concerns and the depletion of fossil fuels. Solar energy has emerged as a promising alternative. In recent years, there has been a significant focus on perovskite solar cells due to their remarkable power conversion efficiencies and their ability to be produced in a cost-effective manner. These cells have attracted considerable attention from researchers and industry professionals alike. However, traditional perovskite materials often contain toxic lead, raising concerns about their environmental impact and long-term sustainability. This article highlights the environmental concerns associated with lead-based perovskite materials and explores the advantages, challenges, and potential of lead-free halide double perovskites as sustainable alternatives for achieving an enlightening and sustainable future in the field of photovoltaics. Lead-free halide perovskites have been an area of active research in the field of nanotechnology and material science due to their potential for various applications. We provide an overview of perovskite solar cells as a promising technology, discussing their material properties and device performance. Furthermore, we present a comparative analysis between lead-based and lead-free perovskites, emphasizing the challenges and future perspectives associated with the development and implementation of lead-free alternatives. Through this analysis, we aim to shed light on the potential of lead-free halide double perovskites and inspire further research in the quest for environmentally friendly materials for solar energy applications.